(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Diabetic Foot Ulcers(DFUs) affect between 5% to 10% of the population. The area of a diabetic foot ulcer is measured manually or semi-automatically. There is no clear procedure for evaluating the foot ulcer region for the purpose of treatment.The problem to be solved is complex due to the various shapes of the ulcers and their position on the foot, which is not necessarily flat and can cover several areas of the foot. In this research work, a combination of Logarithmic Discrete Wavelet Transform (LDWT) within a Symmetric Logarithmic Image Processing Model (S-LIP) model is applied for the contrast enhancement of foot ulcer images and then standard Grab-Cut segmentation algorithm is applied for the Region of Interest (ROI) extraction. The experimental results reveal that the proposed contrast enhancement and segmentation model is best suitable for the diabetic foot ulcer segmentation.